Pengaruh Penggunaan Fungi Mikoriza Arbuskula terhadap Produksi dan Karakteristik Fisiologis Lamtoro Mini (Desmanthus virgatus) pada Tanah Salin: The Effect of The Use of Arbuscular Mycorrhizal Fungi on The Production and Physiological Characteristics of Lamtoro Mini (Desmanthus virgatus) on Saline Soil - Rizki, Agam; Manu Hara Karti , Panca Dewi; Prihantoro, Iwan; Mudastsir; Yaman, M A; Ilham (Departemen Ilmu Nutrisi dan Teknologi Pakan Fakultas Peternakan Institut Pertanian Bogor, 2025)
This study aims to evaluate the quality of Arbuscular Mycorrhizal Fungi (AMF) inoculum produced using various nutrient fortification methods for Desmanthus virgatus plants in helping to cope with salinity stress. This study was conducted at the Agrostology Laboratory of IPB University with a Completely Randomized Design (CRD) Factorial Pattern 5 x 3 with 8 replications. Factor A was types of AMF, namely AMF without administration (JM0), commercial/superior AMF (JMU), AMF fortified with AB Mix 1000 ppm (JM1), AMF fortified with AB Mix 2000 ppm (JM2), and AMF fortified with AB Mix 3000 ppm (JM3). Factor B was levels of soil salinity, namely control soil (JT0), medium saline soil (JT1), and high saline soil (JT2). Each plant was given 20 g of AMF, compost, and NPK fertilizers. Both plants without AMF and with AMF were given different doses of fertilizer, namely 100% dose and 50% dose. The results showed that inoculation of JMU, JM1, JM2 and JM3 had the same AMF colonization consistency in JT0, JT1 and JT2. AMF inoculation of JMU, JM1, JM2, and JM3 effectively increased (p<0.05) the vertical height of Desmanthus virgatus on high saline soil (JT2). The production of dry weight of JM3 shoots on high saline soil (JT2) was the highest (p<0.05) among other treatments. Leaf chlorophyll of JMU, JM1, JM2, and JM3 in control soil (JT0) was significantly higher than JM0, but it was not significantly different in medium saline soil (JT1) and high saline soil (JT2). AMF inoculation with JMU, JM1, JM2, and JM3 effectively reduced leaf proline content in highly saline soil (JT2), while salinity significantly (p<0.05) increased the leaf proline levels of Desmanthus virgatus. The conclusion was that AMF could increase the productivity of Desmanthus virgatus legumes on high-salinity soil. Desmanthus virgatus has an acceptable tolerance level on medium and high saline soils. Arbuscular Mycorrhizal Fungi JM3 (result of AB Mix 3000 ppm fortification) has a better production ability than JM1, JM2, and JMU on high saline soil. Key words: forage crops, marginal land, legumes